Kontekstualisasi Interpretasi Teks Dalil Gender Prespektif Ushul Fiqh - Datmi, Muhammad Akbar Rosyidi (Al-I'jaz: Jurnal Kewahyuan Islam, 2020)
The text of the proposition is an Arabic text that appeared in the past through certain events and specific socio-cultural. Consequently, understanding the text becomes complex especially if it is understood based on the current time and socio-culture. To overcome the complexity of understanding the text, previous scholars have put formulations of understanding which are none other than ushul fiqh in studying the text in order to avoid misunderstanding.This study aims to explore the interpretation of the text in accordance with developments and demands of the time but in line with the rules of understanding that have been formulated by previous scholars.This research is a library research with an approach to collect research data from the literary treasures and make the world of texts, especially the books of Hadith and Usul Fiqh as the main objects of analysis.The results of this study that understand the text of the proposition textually and contextually have fundamental differences in understanding. Understanding text textually is very much bound to text literally and makes comprehension frozen. Unlike the contextual understanding of texts that are not bound to the text and are more in line with the demands of the times. While understanding the text through the ushul fiqh approach, sometimes the results are in accordance with textual understanding, sometimes also according to contextual understanding.The results of this study can be taken into consideration in understanding texts, especially which matan are bound by a particular time and era and are not relevant when applied today.  Fast traslate Icon translate